Fast Broad-Spectrum Staining and Photodynamic Inhibition of Pathogenic Microorganisms by a Water-Soluble Aggregation-Induced Emission Photosensitizer - Zhou, Qi; Lyu, Xiaoming; Cao, Bing; Liu, Xueping; Liu, Jing; Zhao, Jiarui; Lu, Siyu; Zhan, Meixiao; Hu, Xianglong (Frontiers in Chemistry, 2021)
Pathogenic microorganisms pose great challenges to public health, which is constantly urgent to develop extra strategies for the fast staining and efficient treatments. In addition, once bacteria form stubborn biofilm, extracellular polymeric substance (EPS) within biofilm can act as protective barriers to prevent external damage and inward diffusion of traditional antibiotics, which makes it frequently develop drug-resistant ones and even hard to treat. Therefore, it is imperative to develop more efficient methods for the imaging/detection and efficient inhibition of pathogenic microorganisms. Here, a water-soluble aggregation-induced emission (AIE)-active photosensitizer TPA-PyOH was employed for fast imaging and photodynamic treatment of several typical pathogens, such as S. aureus, methicillin-resistant Staphylococcus aureus, L. monocytogenes, C. albicans, and E. coli. TPA-PyOH was non-fluorescent in water, upon incubation with pathogen, positively charged TPA-PyOH rapidly adhered to pathogenic membrane, thus the molecular motion of TPA-PyOH was restricted to exhibit AIE-active fluorescence for turn-on imaging with minimal background. Upon further white light irradiation, efficient reactive oxygen species (ROS) was in-situ generated to damage the membrane and inhibit the pathogen eventually. Furthermore, S. aureus biofilm could be suppressed in vitro. Thus, water-soluble TPA-PyOH was a potent AIE-active photosensitizer for fast fluorescent imaging with minimal background and photodynamic inhibition of pathogenic microorganisms.